Preoperative planning and application of minimally traumatic surgical technique in pilon fractures - Bets, Grygorii; Stoyko, Ivan; Bets, Iryna (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
It is known that in high-energy injuries with resultant pilon fractures the damaged tissues are usually on the brink of viability. The standard of surgical treatment today consists in plate osteosynthesis with wide surgical approaches and use of massive hardware. As result of the above, the limit of viability of the investing tissues often turns to be overstepped and irreversible necrotic suppurative complications develop, reaching 54 %. The purpose of the present work was to find the alternative minimally traumatic tactics during preoperative planning for surgical treatment of pilon fractures with combined use of distraction ligamentotaxis with help of rod devices and reposition osteosynthesis. Absence of prognostically significant necrotic suppurative complications and achievement of acceptable results of bone fragment reposition became the first result of using the suggested tactics in 34 patients with pilon injuries.